Olhares atentos, detalhes orientadores: o lugar da inteligência popular na alfabetização de jovens e adultos - Melo, Elma Nunes de (2015)
This study focuses on processes of manifestation in popular intelligence resources, in order to understand them as orientation to teach and to learn, notedly in literacy of young people and adults. It is possible, through this investigation, to contribute to problematize the ways of success in these domains. This millennium, age of information and challenges driven by continuous technological, economic and cultural transformations, demands a society able to find creative solutions to the literacy problems of young people and adults which, acutely, is part of the planetary history and therefore, Brazilian history. Thus, the main focus of this work is to identify and Annalise the expressions of intelligence, in the use of Métis (a practical intelligence) of illiterate or little literate young people and adults, main subjects of this investigation, residents of the cities Pedras de Fogo in the State of Paraiba and Itambé, in Pernambuco. The basic theoretical and methodological bases is presented by authors such as Ginzburg (1989), Détienne e Vernant (2008), Freire (1992; 2011; 2013) and Gonçalves (2013). That present us guiding perspectives to an attentive, crafty and meticulous know-how, before a promising scenario to be mentally anticipated by the researcher educator in his or her search to make prosper the dialog of knowledge on what is genuine for the student in learning situations. This study shows that in order to go foward with success in the litteracy of young people and adults it is important that the educators have lucidity of what their students think and feel, about what they bring historically with themselves, how their genuine repertory of acquiring knowledge, considered valid by them in front of the difficulties of their lives experiences. It is to the educator, therefore, a smart educative practice, adjusted to the domains of a practical inteligence of the students, in a way that they walk with success in direction to the school knowledge, expanding their expectations as to the results to be achieved.